2014
DOI: 10.1016/j.jbiomech.2014.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Gait analysis in chronic heart failure: The calf as a locus of impaired walking capacity

Abstract: a b s t r a c tReduced walking capacity, a hallmark of chronic heart failure (CHF), is strongly correlated with hospitalization and morbidity. The aim of this work was to perform a detailed biomechanical gait analysis to better identify mechanisms underlying reduced walking capacity in CHF. Inverse dynamic analyses were conducted in CHF patients and age-and exercise level-matched control subjects on an instrumented treadmill at self-selected treadmill walking speeds and at speeds representing þ 20% and -20% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…The morphological and functional abnormalities we report above, particularly in the plantarflexors and SOL, could provide a harbinger of impaired function and fatigue (ie initial reduction in the contractile capabilities of the muscle with consequent clinical symptoms of fatigue) early in the clinical course in CHF. In another recent study (24) we compared the mechanics of walking in CHF with that of healthy matched population. Minimal difference in preferred speed or overall joint kinematics and kinetics were observed between groups, a finding that may possibly be explained by optimization of the mechanical cost of transport (i.e.…”
Section: Recent Studies Relating Plantarflexor Muscle Morphology and mentioning
confidence: 99%
“…The morphological and functional abnormalities we report above, particularly in the plantarflexors and SOL, could provide a harbinger of impaired function and fatigue (ie initial reduction in the contractile capabilities of the muscle with consequent clinical symptoms of fatigue) early in the clinical course in CHF. In another recent study (24) we compared the mechanics of walking in CHF with that of healthy matched population. Minimal difference in preferred speed or overall joint kinematics and kinetics were observed between groups, a finding that may possibly be explained by optimization of the mechanical cost of transport (i.e.…”
Section: Recent Studies Relating Plantarflexor Muscle Morphology and mentioning
confidence: 99%
“…Our results also offer insight into the gait mechanics of CHF patients ( Panizzolo et al, 2014 ). The combination of the shorter SOL muscle fascicles in CHF patients and their greater dorsiflexion during mid-stance of gait ( Panizzolo et al, 2014 ) may cause significantly greater SOL strain.…”
Section: Discussionmentioning
confidence: 74%
“…Other factors, however, are also operative. In particular, a substantial number of studies have demonstrated that the muscles of HF patients are smaller and weaker than those of healthy individuals (2330), with the plantar flexors in particular seeming to be adversely affected (31,32). Somewhat counterintuitively, given the changes in fiber type mentioned previously, HF also results in a significant decrease in the maximal velocity of muscle contraction, and hence an even greater reduction in maximal muscle power (which is the product of force and velocity) (30,33).…”
Section: Causes Of Exercise Intolerance In Hfmentioning
confidence: 99%
“…First, many normal activities of daily living (e.g., getting out of a chair, climbing a flight of stairs, carrying groceries) are heavily dependent upon the ability of muscle to generate significant force and/or power. Second, HF-induced reductions in whole-body exercise capacity are closely associated with these alterations in muscle contractile performance (21,23,26,27,31,34,35). Senden et al (36), for example, found that maximal power output during an incremental cycle ergometer test to fatigue in HF patients was significantly correlated with the strength and endurance of their knee extensors and flexors as assessed using isokinetic dynamometry.…”
Section: Causes Of Exercise Intolerance In Hfmentioning
confidence: 99%